Correlation of Neutrophil-Lymphocyte Ratio with the Evidence of Stroke Haemorrhagic at Tertiary Hospitals - IB Kade Satyagraha; Ni Nyoman Wahyuni; Tjok Istri Parwati; Ratna Kartika; Made Wulan Utami Dewi (WMJ (Warmadewa Medical Journal), 2023)
Stroke is the leading cause of death, disability, and morbidity in the world. Hemorrhagic stroke (HS) prevalence accounts for 10–20% of all strokes, whereas ischemic stroke accounts for 85 percent. Clinical manifestation and numerous biomarkers such as ferritin level, cholesterol level, and lately neutrophil-to-lymphocyte ratio have been suggested as a sign of HS prognosis. It’s also used as a modality for differentiating ischemia from hemorrhagic. The purpose of this study is to assess if there is a link between NLR and HS evidence. A retrospective cross-sectional study was conducted among the medical reports of patients treated with stroke at Sanjiwani Hospital Bali through 2018–2020. The inclusion criteria were complete medical reports in adults≥ 18 years old. Data obtained from the medical record include demographic data, including age, gender, chief complaint, stroke diagnoses based on clinical manifestations, data of leucocytes, neutrophils, lymphocytes, NLR, and results of computed-tomography scanning of the head. Data were analyzed with the Chi-Square test for nominal data and Spearman Correlation test to evaluate the correlation of the leucocyte, neutrophil, lymphocyte, NLR, with the diagnoses. Ninety-six patients’ medical records were evaluated in the current study. Age ≥ 50 years old (85.4%) with the oldest age was 91 years old. The top three chief complaints are hemiparesis (78.1%), a decrease of consciousness (7.3%), and facial palsy (5.2%). We also analyzed the correlation of inflammation parameters using the Spearman correlation test. There is a positive weak correlation between leucocyte count (r: 0.351; p<0.001) and NLR with evidence of HS (r = 0.371; p<0.001). The correlation between neutrophil counts and evidence of HS is a positive moderate correlation (r = 0.408, p<0.001). Lymphocyte count has a strong positive correlation with HS (r: 1.000, p = 0.017). The leucocyte, neutrophil, lymphocyte, and NLR are able to predict the evidence of hemorrhagic disease in resource-limited countries.